A synthetic coumarin–thiosemicarbazone hybrid as a high-efficiency copper corrosion inhibitor: Adsorption mechanisms and molecular-level insights - Mohammad Alwi, Muhammad Ammar; Ahmad, Mohammad Norazmi; Mat Piah, Mohd Bijarimi; Pauzi, Hariy; Abdullah, Erna Normaya (Elsevier, 2025)
A coumarin–thiosemicarbazone (CT) hybrid was synthesized and characterized via FTIR, ¹H NMR, and ¹³C NMR spectroscopy. The compound was obtained via Schiff base condensation of 3-acetyl coumarin and thiosemicarbazide in refluxing ethanol with glacial acetic acid as catalyst. The corrosion inhibition efficiency of CT on copper in hydrochloric acid was optimized using response surface methodology (RSM), achieving 97.15 % under optimal conditions (40.10 ◦C, 3.10 M HCl, 0.51 mM CT, 15.76 h immersion time). Adsorption studies revealed that CT undergoes spontaneous chemisorption, supported by Langmuir isotherm fitting and a negative Gibbs free energy (ΔG◦_ads = –39.95 kJ mol⁻¹). SEM and XPS analyses confirmed the formation of a protective CT film as well as Cu–N/Cu–S interactions. Electrochemical impedance spectroscopy (EIS) and polarization studies showed increased charge transfer resistance and reduced corrosion current density. Quantum chemical calculations revealed that CT possesses a narrow HOMO–LUMO gap (2.676 eV), high softness (0.748 eV⁻¹), and high electrophilicity (ω = 20.70 eV), indicating strong surface reactivity. Fukui function and XPS analysis showed that nitrogen and sulfur atoms were key adsorption sites. Molecular dynamics simulations supported its adsorption stability, with an interaction energy of –265 kJ/mol. This study demonstrates that CT is a highly efficient, surface-active inhibitor and offers molecular-level insights into its protection mechanism for copper in acidic environments.